(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes a number of works carried out by the authoritarian Soviet regime in the territory of Uzbekistan in the 20s and 30s of the 20th century to end illiteracy. Also, this article highlights the fact that the Bolsheviks portrayed the local population as completely illiterate, their policy of disregarding their great achievements in science, and the fact that the local women were active in this regard, but in the end they were also repressed.